The Development Of Hypnotherapy Based - Interpersonal Communication Model For Students Suffered From Game Addiction - Imma Rachayu; Azizatul Banat (Universitas Negeri Makassar, 2020)
The purpose of this study is to produce a hypnotherapy-based interpersonal communication model for students who have contracted online games to improve the students' academic achievement at PTIK Dehasen University Bengkulu. The research method was used in development research with limited trials. The results of this limited trial, had aspects determined to state that the hypnotherapy-based interpersonal communication model developed is effective, efficient and practical have been fulfilled, then the development cycle to get an effective, efficient and practical therapy model has ended. This study can be concluded that the hypnotherapy-based communication model is able to reduce the level of online game addiction gradually and consistently, and can influence students' attitudes, opinions and behavior in a dialogic manner and have a positive impact of mental relaxation and a continuous learning spirit so that student academic achievement can increase significantly.